I am having trouble proving that two multivariate formulas are equivalent. I implemented them in MATLAB and numerically they appear to be equivalent.(adsbygoogle = window.adsbygoogle || []).push({});

I would appreciate any help on this.

Prove A = B

A= (Σπ^-1 + Σy^-1)^-1 * (Σπ^-1*π + Σy^-1*y)

y = π+ X*β

Σπ =τ*Σ

Σy = X' * Σβ * X + Σε

B= (Σπ^-1 + P'*Σβ^-1*P)^-1 * (Σπ^-1*π + P'*Σβ^-1*q)

q = P*y

P = (X'*Σ^-1*X)^-1*X'*Σ^-1

Assumptions

i) Σε is infinitesimally small. (If Σε is exactly zero, then Σy may not be invertible).

ii) N > F (If N = F, then the proof is trivial. If N < F then is probably not invertible and P is not defined.)

Notation

A, B: Nx1

π: Nx1

y: Nx1

q: Fx1

β: Fx1

Σ: NxN

Σπ: NxN

Σy: NxN

Σβ: FxF

Σε: NxN

X: NxF

P: FxN

τ: 1x1

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Proving a linear algebra equation

Loading...

Similar Threads - Proving linear algebra | Date |
---|---|

I Proving a set is linearly independant | Apr 14, 2017 |

I Proving a lemma on decomposition of V to T-cyclic subspace | Mar 16, 2017 |

I Proving an inverse of a groupoid is unique | Jan 1, 2017 |

Proving dependent columns when the rows are dependent | Sep 3, 2015 |

Proving vectors are in the column space | Oct 30, 2014 |

**Physics Forums - The Fusion of Science and Community**